2015
DOI: 10.1097/gox.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study to Evaluate the Functional Effect of Unilateral Uvuloplasty after Primary Palatoplasty

Abstract: Background:The conventional method for uvular repair suturing the 2 hemi-uvulas of the palatal cleft together in the midline does not allow us to obtain a proper anatomical repair. In our hands, the midline straight closure frequently causes retraction of the uvular tissues with the consequent abnormal appearance of the uvula. We described before a method for uvular repair in patients with cleft palate. The technique consists in preserving one of the hemi-uvulas, which is moved to the midline to form the defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Any lengthening of the palate anticipated from this technique is posterior to the position of the reconstructed levator sling (levator knee) and is not expected to increase the functional length of the velum which closes against the posterior pharyngeal wall. This is in contrast to the 2 studies by Rossell-Perry who was seeking a functional effect and found better speech in 1 of the 2 studies (Rossell-Perry, 2015). We hope that our reply clarifies the confusion.…”
contrasting
confidence: 84%
“…Any lengthening of the palate anticipated from this technique is posterior to the position of the reconstructed levator sling (levator knee) and is not expected to increase the functional length of the velum which closes against the posterior pharyngeal wall. This is in contrast to the 2 studies by Rossell-Perry who was seeking a functional effect and found better speech in 1 of the 2 studies (Rossell-Perry, 2015). We hope that our reply clarifies the confusion.…”
contrasting
confidence: 84%
“…5 The aesthetic and functional outcomes of this method have been studied previously, reducing the velopharyngeal space and improving velopharyngeal function. 7 In the present study, the velar muscles were repaired, preserving the tensor veli palatini attachments to the hamulus. The rate of mild-to-severe velopharyngeal insufficiency in the present study was acceptable and lower than that (8.7%) among patients who underwent conventional intravelar veloplasty performed by the same surgeon.…”
Section: Discussionmentioning
confidence: 97%
“…The two-flap palatoplasty group underwent Bardach’s two-flap palatoplasty 18 plus the Sommerlad type of intravelar veloplasty 21 and unilateral uvuloplasty. 22 , 23 …”
Section: Methodsmentioning
confidence: 99%